HASIL BELAJAR IPS TERPADU ANTARA MODEL PEMBELAJARAN KOOPERATIF TALKING STICK DAN TSTS - Lailiyah Lailiyah; Nurdin Nurdin; Darwin Bangun (FKIP Unila, 2015)
Comparative study on the results of an social studies knowledge ability, the ability of social attitudes, and Traffic speaking skills between cooperative learning model talking stick and two stay two stray (ts-ts). The method used is a quasi-experiment. Test hipotesis using multivariate of variance. Based on data analysis: average student achievement in a working knowledge of the type of cooperative learning model talking stick is lower than students who studied using the model of cooperative two stay two stray. The average student achievement in social attitudes and abilities on the ability of speaking skills are learned using cooperative models talking stick is higher than students who studied using the model of cooperative two stay two stray. Penelitian komparatif hasil belajar IPS terpadupada kemampuan pengetahuan, kemampuan sikap sosial, dan kemampuan keterampilan berbicarasiswa yang pembelajarannya menggunakan model pembelajaran kooperatif tipe talking stick dan two stay two stray (ts-ts). Metode yang digunakan adalah eksperimen semu. Uji hipotesis menggunakan analisis multivariate of varian. Berdasarkan analisis data diperoleh: rata-rata hasil belajar siswapada kemampuan pengetahuan yang pembelajarannya menggunakan model kooperatif tipe talking stick lebih rendah dibandingkan dengan siswa yang pembelajaranya menggunakan model kooperatif tipe two stay two stray, rata-rata hasil belajar siswa pada kemampuan sikap sosial dan pada kemampuan keterampilan berbicara yang pembelajarannya menggunakan model kooperatif tipe talking stick lebih tinggi dibandingkan dengan siswa yang pembelajaranya menggunakan model kooperatif tipe two stay two stray.Kata kunci: belajar, hasil belajar, talking stick, two stay two stray